Cohort Profile: The Danish Testicular Cancer Late Treatment Effects Cohort (DaTeCa-LATE) - Kreiberg, Michael; Bandak, Mikkel; Lauritsen, Jakob; Skøtt, Julie Wang; Johansen, Nanna Borup; Agerbaek, Mads; Holm, Niels Vilstrup; Johansen, Christoffer; Daugaard, Gedske (Frontiers in Oncology, 2018)
The cohort was set up in order to analyse late effects in long-term testicular cancer survivors (TCS) and to contribute to the design of future follow-up programs addressing and potentially preventing late effects. Data for this cross-sectional study was collected between 1 January 2014 and 31 December 2016 among living Danish TCS and 60% agreed to participate in the cohort (N = 2572). Mean time since testicular cancer diagnosis was 18 years (range 7-33) and mean age of participants was 53 years (range 25-95). Data consists of results of a questionnaire with patient reported outcomes which covers a broad range of items on late-effects. The study also included data obtained through linkages to Danish registries, a biobank, and clinical data from hospital files and pathology reports originating from the Danish Testicular Cancer Database (DaTeCa). The treatment during the observation period has been nearly the same for all stages of TC and is in agreement with today’s standard treatment, this allows for interesting analysis with a wide timespan. We have extensive data on non-responders and are able to validate our study findings. Data from a Danish reference population (N = 162 283) allows us to compare our findings with a Danish background population. The cohort can easily be extended to access more outcomes, or include new TCS. A limitation of the present study is the cross-sectional design and despite the large sample size, DaTeCa-LATE lacks statistical power to study very rare late effects. Since it was voluntary to participate in the study we have some selection bias, for instance we lack responders who were not in a paired relationship, but we would still argue that this cohort of TCSs is representative for TCSs in Denmark. Collaboration and data access: Researches interested in collaboration with the DaTeCa-LATE study group please contact Professor Gedske Daugaard kirsten.gedske.daugaard@regionh.dk.